ผลการจัดกิจกรรมเสริมสร้างการตัดสินใจในนักเรียนประถมศึกษา: กรณีศึกษาผลด้วยการทดสอบ Iowa Gambling Task™, Version 2 (IGTTM2) - ภู่บำรุง, โสภิตา; ทรัพย์วิระปกรณ์, วรากร; ศิริธาดากุลพัฒน์, ศศินันท์ (วารสารวิจัยทางการศึกษา คณะศึกษาศาสตร์ มหาวิทยาลัยศรีนครินทรวิโรฒ, 2020)
บทคัดย่อ การวิจัยครั้งนี้มีจุดมุ่งหมายเพื่อศึกษาผลการจัดกิจกรรมเสริมสร้างการตัดสินใจในนักเรียนประถมศึกษา กลุ่มตัวอย่างได้แก่ นักเรียนชั้น ป. 6 จำนวน 60 คน สุ่มอย่างง่ายและจับคู่คะแนนเข้ากลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 30 คน เครื่องมือวิจัย ได้แก่ 1) กิจกรรมเสริมสร้างการตัดสินใจในนักเรียนประถมศึกษาที่ผู้วิจัยสร้างขึ้น 2) แบบทดสอบ Iowa Gambling Task™, Version 2 (IGT™2) กลุ่มทดลองได้รับกิจกรรมเสริมสร้างการตัดสินใจ จำนวน 8 ครั้ง ๆ ละ 50 นาที ส่วนกลุ่มควบคุมได้รับการเรียนการสอนตามปกติ ทดสอบ IGT™2 เพื่อวัดผลการทดลอง 3 ระยะ ได้แก่ ก่อนการทดลอง หลังการทดลอง และติดตามผลหลังการทดลอง 3 สัปดาห์ สถิติที่ใช้คือการวิเคราะห์ความแปรปรวนแบบวัดซ้ำหนึ่งตัวแปรระหว่างกลุ่มและหนึ่งตัวแปรภายในกลุ่ม และทดสอบความแตกต่างรายคู่แบบบองเฟอรอนีผลการวิจัยพบว่า 1) มีปฏิสัมพันธ์ระหว่างวิธีการทดลองกับระยะเวลาของการทดลองอย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2) นักเรียนที่ได้รับการจัดกิจกรรมเสริมสร้างการตัดสินใจสำหรับนักเรียนชั้นประถมศึกษา มีคะแนนการตัดสินใจหลังการทดลองสูงกว่าก่อนการทดลอง อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 และ 3) นักเรียนที่ได้รับการจัดกิจกรรมเสริมสร้าง การตัดสินใจสำหรับนักเรียนชั้นประถมศึกษา มีคะแนนการตัดสินใจในระยะติดตามผลสูงกว่าก่อนการทดลอง อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 สรุปได้ว่า การจัดกิจกรรมเสริมสร้างการตัดสินใจในนักเรียนประถมศึกษามีประสิทธิภาพใน การเพิ่มทักษะการตัดสินใจในนักเรียนประถมศึกษา คำสำคัญ: การตัดสินใจ การจัดกิจกรรมเสริมสร้างตัดสินใจ นักเรียนชั้นประถมศึกษา ABSTRACT The purpose of this research was to study the effects of the decision making activities for elementary school students. The samples consisted of 60 Grade 6th students. The samples were randomly selected and assigned by matched scores into the experimental group and control group, 30 persons a group. The research instruments were; 1) the decision making activities for elementary school students created by the researcher, and 2) the Iowa Gambling Task™, Version 2 (IGT™2). The experimental group received 8 times of the activities, 50 minutes a time. The control group received an ordinary teaching activity. The assessment tool was IGT™2 for assessing 3 phases: pretest, posttest, and 3-week-follow-up. The statistics used for analyzing data were the variance analysis with the repeated measure, one between-subject variable and one within-subject variable, and the pair test with Bonferroni. The results of this study were as follows: 1) There was the interaction between the research method and experimental time at the statistically significant level of .05, 2) the students received the decision making activities had higher decision making scores in posttest than that in pretest at the statistically significant level of .05; and, 3) the students who received the decision making activities had higher decision making scores in follow-up than those in pretest at the statistically significant level of .05. In conclusion, the organization of decision-making activities in elementary school students was effective to increase decision-making skills in the elementary school students. Keywords: Decision Making, the Organization of Decision Making Activities, Elementary School Students